Identification of the factors influencing the profitability of the Hungarian beer industry - Jantyik Lili; Török Áron; Balogh Jeremiás Máté (University of Szeged, Faculty of Agriculture Szeged, 2019)
Beer consumption and beer industry is an important beverage sector in Hungary because the beer is the most consumed alcoholic beverage in the country according to WHO studies. During history, breweries developed in different size and different values. The Hungarian beer industry can be divided into three groups of breweries: old large scale breweries, old microbreweries and new wave microbreweries. In this paper, we examine the factors influencing the economic performance of the Hungarian beer industry based on panel data of all active Hungarian breweries in 2018 (121 breweries), for the period of 2009-2017. The study applied panel-data linear models by using feasible generalized least squares with error structure with no cross-sectional correlation option. The economic performance is measured by companies’ turnover, EBIT and profit, which were used as dependent variables. The following explanatory variables were applied in the model: age of brewery (number of closed business years), Social Media activity (FB likes of company page), geographical location (distance from Budapest in km), direct sales (represent own pub/direct sales channel), impact of tax reduction (small beer companies pay 50% less tax since 2012). Regression results have shown a number of determinants of the economic performance of Hungarian breweries, and the estimations are valid for all profitability indicators included (turnover, EBIT and profit). As in previous research, we have come to the conclusion that if the company survives the early years of operation, we can expect profitable activity. Since the ratio of early bankruptcy among Hungarian brewers is still very high, the fluctuation between smaller breweries strongly determines the industry.The benefits of short food supply chains (both physical distance and number of intermediaries) are also prevalent in the beer industry. Breweries with direct sales channels (mostly their own pubs) showed significantly higher sales, EBIT and profits compared to those selling their products by third parties. Breweries situated in Budapest are the most profitable, because the capital city provides a higher demand for high-quality beer, in contrast, the distance from the capital city has a negative impact on the firm’s success.The Social Media activity, often used as the only promotion channel for the microbreweries, has a positive impact on the brewery’s profitability. Finally, tax reduction for small breweries introduced in 2012 by the Hungarian government had the most important positive impact on industrial profitability, especially in the case of microbreweries. It seems the government aim to support small scale beer production has been successful because it helped the survival of the Hungarian microbreweries.
Keywords: Társadalomtudományok; Közgazdasági és gazdálkodástudományok